The recombinant IL-35 and anti-Ebi3 antibody administration before implantation modulate immune regulation and fetal outcomes in an abortion-prone mouse model - Slawek, Anna; Kubik, Paulina; Psurski, Mateusz; Kedzierska, Anna Ewa; Chelmonska-Soyta, Anna (Frontiers in Immunology, 2025)
IntroductionInterleukin-35 (IL-35), consisting of two subunits - Ebi3 and p35, is a pleiotropic anti-inflammatory cytokine implicated in fetal tolerance and pregnancy maintenance. Reduced IL-35 levels in abortion-prone mice and women with recurrent miscarriage suggest its deficiency contributes to pregnancy failure. In abortion-prone mice, IL-35 administration during mid-term gestation rescued pregnancy. However, it is unclear whether IL-35 administration before implantation (during the time of the first recognition of paternal antigens) can expand regulatory lymphocyte pools and restore maternal tolerance. Therefore, this study aimed to investigate the influence of intraperitoneal administration of recombinant IL-35 (rIL-35) and anti-Ebi3 antibody shortly after mating on successful pregnancy, fetal blood flow, and the profiles of several types of regulatory cells in a murine abortion-prone model.MethodsrIL-35 and anti-Ebi3 antibody were administered on 0 days post coitum (dpc). The embryos were imaged in PW Doppler mode on the 14th day of pregnancy. The frequencies of different subpopulations of Bregs (B10, MZ, T2-MZP, FO), Tregs, iTr35, γδ T, Th17 and NK cells were measured in uterine-draining lymph nodes, spleens and decidua using flow cytometry. The concentrations of Th1/Th2/Th17 cytokines in the serum were analyzed.ResultsThe main finding of our study is that we did not observe any differences in abortion rates between the groups. In the group that received the neutralizing antibody, a lower embryonic heart rate, lower circulatory competence of the fetal placenta, and elevated serum Th17/Th2 cytokine concentrations were observed. IL-35 administration increased the frequency of B10 and IL-35-producing B10 and regulatory T cells at the periphery and NKIL-35+ and CD19+IL-35+ but not Treg cells in the decidua.ConclusionsA single administration of IL-35 shortly after mating, does not have an anti-abortion effect. It exhibits a multifaceted effect on immune regulatory cells and IL-35 neutralization results in decreased embryonic heart rate and impaired placental–fetal circulation.